Study on the wettability and tribological behaviors of glass fiber reinforced poly(ether-ether-ketone) against different polymers as bearing materials for artificial cervical disc. (December 2015) - Song, J.; Liu, Y.H.; Wang, S.; Liao, Z.H.; Liu, W.Q.
Abstract: The poly(ether-ether-ketone) (PEEK) material is of great interest as an alternative to conventional metal and polymer materials in orthopedics because of its prominent biocompatibility and low elastic modulus. In this paper, tribological behaviors of glass fiber reinforced PEEK (GFRPEEK) against ultra-high molecular weight polyethylene (UHMWPE) and polytetrafluoroethylene (PTFE) were tested in a ball-on-disc contact configuration under dry friction and 25% (v/v) newborn calf serum (NCS) lubricated conditions. The static contact angle, surface damage topography, and wear parameter of wear tracks were studied. For comparison, the characteristics of unaltered PEEK were also investigated. The results suggested that the wettability of PEEK was improved by glass fiber reinforcement. After glass fiber reinforcement, the friction coefficients of the friction bearings were decreased under dry friction condition and increased under 25% NCS lubricated condition. Compared with those of the unaltered PEEK, the wear volumes of GFRPEEK both in dry friction and 25% NCS lubricated conditions were reduced. In addition, the GFRPEEK-on-UHMWPE friction bearing demonstrated optimum tribological properties and could be applied as bearing materials for artificial cervical disc. Highlights: Glass fiber reinforcement could improve the friction coefficients in dry friction. Glass fiber reinforcement could increase the friction coefficients in 25% newborn calf serum lubrication. The glass fibers introduced in PEEK relieved the deformation of the surfaces as well as the plowing effect. The UHMWPE–GFRPEEK could be applied as bearing materials for artificial cervical disc.